How being a design-driven company will get you from good to great - Brunner, Robert 1958- (FTPress Delivers, 2010)
This Element is an excerpt from Do You Matter?: How Great Design Will Make People Love Your Company (ISBN: 9780137142446) by Robert Brunner and Stewart Emery. Available in print and digital formats. Building the shared understandings, values, and commitments that make for a truly outstanding design- and experience-driven company. You need a development process that centers on people and experience. You need to incent everyone to be part of it. You need a marketing process that can communicate those ideas, with design integral to it all. And you need an engineering system that understands that design values are part of the marketing, engineering, manufacturing, and delivery equations ...
Excerpted from: Do You Matter? / by Robert Brunner and Stewart Emery. Cf. resource description page (viewed March 3, 2010). - Includes bibliographical references
Keywords: Industrial design; New products; Industrial design coordination; Branding (Marketing); Design; Design; Coordination; Stratégie de marque; branding; ART; Folk & Outsider Art; CRAFTS & HOBBIES; Folkcrafts